The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3847/1538-4365/ab174f
|View full text |Cite
|
Sign up to set email alerts
|

The QUEST-La Silla AGN Variability Survey: Selection of AGN Candidates through Optical Variability

Abstract: We used data from the QUEST-La Silla Active Galactic Nuclei (AGN) variability survey to construct light curves for 208,583 sources over ∼ 70 deg 2 , with a a limiting magnitude r ∼ 21. Each light curve has at least 40 epochs and a length of ≥ 200 days. We implemented a Random Forest algorithm to classify our objects as either AGN or non-AGN according to their variability features and optical colors, excluding morphology cuts. We tested three classifiers, one that only includes variability features (RF1), one t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…The four diagrams show that our RF5 AGN candidates are generally characterized by redder colors than the AGN in our LS. This suggests that variability-based selection is quite effective in identifying host-dominated AGN, consistent with the findings of Sánchez-Sáez et al (2019, and highlights the strength of variability-based selection of AGN over color selection, which easily misses host-dominated AGN as their colors are similar to those of inactive galaxies.…”
Section: Classification Of the Unlabeled Setsupporting
confidence: 80%
See 2 more Smart Citations
“…The four diagrams show that our RF5 AGN candidates are generally characterized by redder colors than the AGN in our LS. This suggests that variability-based selection is quite effective in identifying host-dominated AGN, consistent with the findings of Sánchez-Sáez et al (2019, and highlights the strength of variability-based selection of AGN over color selection, which easily misses host-dominated AGN as their colors are similar to those of inactive galaxies.…”
Section: Classification Of the Unlabeled Setsupporting
confidence: 80%
“…The code we use to apply an RF algorithm to our sample of sources takes its cue from the one used in Sánchez-Sáez et al (2019). It is based on the use of the Python RF classifier library 4 included in the scikit-learn library, which provides a number of tools for machine learning-based data analysis (Pedregosa et al 2011).…”
Section: Rf Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra were reduced using the PESSTO NTT pipeline. 1 There was also one spectrum taken by the Goodman High Throughput Spectrograph at the Southern Astrophysical Research telescope (SOAR) (Clemens, Crain & Anderson 2004), reduced using the dedicated pipeline (Sánchez-Sáez et al 2019). The final reduced and calibrated spectra will be available on the Weizmann Interactive Supernova Data Repository (WISeREP; .…”
Section: Data Reductionmentioning
confidence: 99%
“…More recently Sánchez-Sáez et al (2019) have shown that using variability and colors not only is more effective than using colors only, but that a new population of redder AGN can be identified. This population appears to be dominated by low-luminosity AGN, with colors some times completely dominated by the host emission.…”
Section: Selecting Agn Through Variabilitymentioning
confidence: 99%